Desnutrición como factor de riesgo para parto pretérmino en gestantes del Hospital Regional de Loreto periodo 2021 a 2023 - Gonzales Loayza, Percy Raul (2024)
The present work will study malnutrition in women during the physiologically demanding period of pregnancy and which would lead to a greater risk of suffering spontaneous abortions and giving birth to low-weight or premature neonates. Since premature birth. The problem raised in this work is: Is malnutrition a risk factor for preterm births in pregnant women at the Loreto Regional Hospital in the period 2021 to 2023? And the General Objective is to show that malnutrition is a risk factor for preterm births in pregnant women at the Loreto Regional Hospital in the period from 2021 to 2023, also to demonstrate the frequency it occurs in those who have malnutrition and those who do not. have malnutrition and make a comparison between those exposed and not exposed to the problem of malnutrition. The importance is that premature neonates generate a very high cost to the health sector, parents and society; Therefore, the prediction and prevention of premature births is important and a priority. The causes of premature birth are multifactorial and poverty, demographic and obstetric factors contribute, but in many cases a specific cause is not found. The study population will be pregnant patients treated in the gynecology obstetrics service of the Loreto Regional Hospital during the period 2021 to 2023; with malnutrition and without malnutrition, aged between 20 – 35 years, a single fetus and with a complete medical history; overweight pregnant women are not included; obesity; hypertensive disease of pregnancy; urinary tract infections, anemia; nephrotic syndrome, liver cirrhosis, heart failure. The technique and work method will be carried out by selecting pregnant patients from the Loreto Regional Hospital during the period from 2021 to 2023 and authorization will be requested; identify pregnant patients to be included in the study based on the BMI value during their first trimester of pregnancy to characterize the malnutrition variable, which will be corroborated by reviewing their clinical history; Afterwards, we will proceed to identify the gestational week of completion of labor to assess the outcome of preterm labor. The variables that will intervene are identified by recording them on the data collection sheet; Then the information is processed with a statistical analysis, all the information will be tabulated and the results will be interpreted with the instruments used. The frequency distribution data will be obtained for the qualitative variables in the analytical statistics, the chi-square test will be used, which will be considered significant if chance is less than 5% (p<0.05). the study's own statistician to obtain the relative risk with its 95% confidence interval and the multivariate analysis with logistic regression. As an ethical aspect, the declaration of Helsinki II24 and the General Health Law25 will be used. The privacy and confidentiality of research subjects is respected